Melkersson-Rosenthal Syndrome with Orofacial Swelling and Recurrent Lower Motor Neuron Facial Nerve Palsy: A Case Report and Review of the Literature - Jerome Okudo; Yemi Oluyide (Case Reports in Otolaryngology)
Melkersson-Rosenthal Syndrome (MRS) is a rare otoneurologic condition, which is poorly understood and often underdiagnosed. Etiology and incidence are unclear, although infectious, inflammatory, and genetic causes have been implicated. Recurrent facial nerve palsy, facial swelling, and fissured tongue are the symptoms and signs of this condition. However, this triad is not typical in all patients as patients may present with one or more of the symptoms, which makes management of this condition difficult. Steroids may prove to be useful especially in patients who have facial nerve palsy. In this case report, we have described a 46 year-old Caucasian male who presented to the clinic for the evaluation of orofacial swelling and left facial deviation with a history of multiple treatments for recurrent lower motor neuron type facial nerve palsy.